Keanekaragaman dan Analisis Vegetasi Menggunakan Pola Kuadran dalam Ekologi Tumbuhan - Mulya, Baginda; Agatha, Gabriella Jessica (TSAQOFAH, 2026)
Studies on diversity and vegetation structure have been widely conducted in plant ecology, yet research that specifically examines variation in plant community structure based on different quadrat sizes at a single observation site remains relatively limited. This study aimed to analyse the composition, structure, and dominance of plant vegetation using the quadrat method at several observation scales. A descriptive quantitative approach with a field survey design was employed by placing 2 × 2 m and 5 × 5 m quadrat plots along transect lines determined systematically with a random starting point. Data were collected through direct observation and recording of the number of individuals, frequency of occurrence, density, dominance, and the Importance Value Index (INP) of each plant species, and then analysed quantitatively to characterise the structure of the vegetation community at each growth level. The results showed differences in species composition and dominance patterns for each quadrat size, with strong dominance by several particular species both in the understorey strata and at the sapling and shrub levels. These findings enrich understanding of the relationship between observation scale and vegetation community structure and underscore the importance of using varied quadrat sizes in vegetation analysis. This study also provides practical implications as baseline ecological data to support the management and monitoring of plant diversity at the local level, as well as opening opportunities for further research with broader spatial and temporal coverage.